Analisis Terhadap PenegakAnalisis Penegakan Hukum Pemilu Dalam Perspektif UU No 7 Tahun 2017 - vanessa vanessa octavia (Jurnal Mitra Prima, 2020)
Abstract The title of this is article is "Analysis of Election Law Enforcement in the Perspective of Law No. 7 of 2017" The main problem we raised is how the KPU faces changes to Law No. 15 of 2011 concerning election administrators and Law Number 8 of 2012 concerning the election of DPR, DPD and DPRD Members into Law Number 7 of 2017 and what are the challenges faced by KPU in the Implementation of Laws Number 7 of 2017. In this paper the method we used is quantitative analysis that gives an overview of an object through certain analytical techniques. The ways that can be done by the KPU in dealing with changes to Law Number 15 Year 2011 concerning election administrators and Law Number 8 of 2012 concerning the election of DPR, DPD and DPRD Members become Law Number 7 Year 2017. Something that can be made are involving electoral institutions, which in this case is the Bawaslu (Election Supervisory Body) and its ranks. Therefore, Bawaslu must increase strict supervision in the administration of elections. Keywords: how to deal with changing laws, challenges faced by the KPU, Law Number 7 of 2017